2016
DOI: 10.1007/s13361-016-1495-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Carbohydrates and Related Materials Using Sodium Ion Adducts Produced by Matrix-Assisted Laser Desorption Ionization

Abstract: Abstract. The utility of sodium ion adducts produced by matrix-assisted laser desorption ionization for the quantification of analytes with multiple oxygen atoms was evaluated. Uses of homogeneous solid samples and temperature control allowed the acquisition of reproducible spectra. The method resulted in a direct proportionality between the ion abundance ratio I([A + Na] + )/I([M + Na] + ) and the analyte concentration, which could be used as a calibration curve. This was demonstrated for carbohydrates, glyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Nevertheless, the authors found that the use of these ions from both sample and matrix produced similar results for quantification. Calibration curves were essentially linear over three orders of magnitude with results reported from stachyose ( 1/19 ), and the N ‐glycans Man 5 GlcNAc 2 ( 39 ) and a fucosylated biantennary complex glycan ( 40 ) (Ahn et al, 2016).
…”
Section: Quantificationmentioning
confidence: 52%
“…Nevertheless, the authors found that the use of these ions from both sample and matrix produced similar results for quantification. Calibration curves were essentially linear over three orders of magnitude with results reported from stachyose ( 1/19 ), and the N ‐glycans Man 5 GlcNAc 2 ( 39 ) and a fucosylated biantennary complex glycan ( 40 ) (Ahn et al, 2016).
…”
Section: Quantificationmentioning
confidence: 52%
“…The sample was incubated with (b) 1 μg/mL KatG for 15 min and (c) 1 μg/mL KatG supplemented with 5 mg/mL glucose oxidase and 5 mM glucose for 15 min. Sodium ion adducts of carbohydrates are a well-documented product of MALDI …”
Section: Resultsmentioning
confidence: 99%